Copper and Cobalt Ions Released from Metal Oxide Nanoparticles Trigger Skin Sensitization - Kim, Sung-Hyun; Lee, Jin Hee; Jung, Kikyung; Yang, Jun-Young; Shin, Hyo-Sook; Lee, Jeong Pyo; Jeong, Jayoung; Oh, Jae-Ho; Lee, Jong Kwon (Frontiers in Pharmacology, 2021)
Metal oxide nanoparticles (NPs) constitute one of the major types of nanomaterials (NMs) that are used in industrial, biomedical, and cosmetic applications. With an increase in the number and production volume of NPs, concerns regarding their toxicity have also increased exponentially in the recent years. This study aimed to evaluate the skin sensitization induced by metal oxide nanoparticles (NPs), using an alternative method. We selected five metal oxide NPs, containing copper oxide, cobalt monoxide, cobalt oxide, nickel oxide, or titanium oxide, and two types of metal chlorides (CoCl2 and CuCl2), to compare the skin sensitization abilities between NPs and the constituent metals. The materials were applied to KeratinoSensTM cells for imitated skin-environment setting, and luciferase induction and cytotoxicity were evaluated at 48 h post-incubation. In addition, the response of metal oxide NPs was confirmed in lymph node of BALB/C mice via an in vivo method. The results showed that CuO and CoO NPs induce a similar pattern of positive luciferase induction and cytotoxicity compared to the respective metal chlorides; Co3O4, NiO, and TiO2 induced no such response. Collectively, the results implied fast-dissolving metal oxide (CuO and CoO) NPs release their metal ion, inducing skin sensitization. However, further investigations are required to elucidate the mechanism underlying NP-induced skin sensitization. Based on ion chelation data, metal ion release was confirmed as the major ‘factor’ for skin sensitization.